The Survival Strategy of Households Affected by Tidal Floods: The Cases of Two Villages in the Pekalongan Coastal Area - Harini, Rika; Susilo, Bowo; Sarastika, Tiara; Supriyati, S; Satriagasa, M C; Ariani, Rina Dwi (Forum Geografi, 2017)
Pekalongan is one of the coastal areas of Java Island that is affected by tidal floods. Tidal floods have various impacts on the social and economic conditions of the community, thus affecting their livelihoods. The purpose of this study was to examine the impact of a tidal flood, the socioeconomic characteristics of the community and the survival approach of coastal communities in Pekalongan. This study was conducted using a purposive sampling method in two villages in Pekalongan Regency, namely Jeruksari Village and Tegaldowo Village, because these two areas are affected by tidal floods. The study was conducted by using in-depth interviews and focus group discussions (FGDs), as well as structured interviews. The structured interview sample consisted of 60 respondents who were selected at random using quota sampling. The analysis was using qualitative-descriptive and quantitative methods. The gathered data were then presented in tables, diagrams and maps. The results showed that tidal floods resulted in physical, economic, sociocultural, health, educational, and environmental damages to the communities in both villages. The majority of the community members only have an elementary school education and primarily work as labourers. There is a difference in the amount of family income between the two villages, where the average family in Jeruksari Village has a higher income (IDR 3,465,300 per month) than the average family in Tegaldowo Village with total household income of about IDR 2 million per month. The most frequently used approach for survival in both villages is what is known as the survival strategy, i.e. a strategy to meet the needs of life at a minimum level to survive.